Identification of a Metabolism-Related Signature for the Prediction of Survival in Endometrial Cancer Patients - Fan, Yuan; Li, Xingchen; Tian, Li; Wang, Jianliu (Frontiers in Oncology, 2021)
Objective: Endometrial cancer (EC) is one of the most common gynecologic malignancies. The present study aims to identify a metabolism-related biosignature for EC and explore the molecular immune-related mechanisms underlying the tumorigenesis of EC. Methods: Transcriptomics and clinical data of EC were retrieved from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases. Common differentially expressed metabolism-related genes were extracted and a risk signature was identified by using the least absolute shrinkage and selection operator (LASSO) regression analysis method. A nomogram integrating the prognostic model and the clinicopathological characteristics was established and validated by a cohort of clinical EC patients. Furthermore, the immune and stromal scores were observed and the infiltration of immune cells in EC cells was analyzed. Results: Six genes including CA3, HNMT, PHGDH, CD38, PSAT1 and GPI, were selected for the development of the risk prediction model. The Kaplan-Meier curve indicated that patients in the low-risk group had considerably better OS (P = 7.874e-05). Then a nomogram was constructed and could accurately predict the OS (AUC=0.827, 0.821, 0.845 at 3-, 5- and 7-year of OS). External validation with clinical patients showed that patients with low risk scores had a longer OS (p=0.04). Immune/stromal scores and infiltrating density of six types of immune cells were lower in high-risk group. Conclusions: In summary, our work provided six potential metabolism-related biomarkers as well as a nomogram for the prognosis of EC patients, and explored the underlying mechanism involved in the progression of EC.